2014
DOI: 10.1055/s-0034-1390757
|View full text |Cite
|
Sign up to set email alerts
|

Primary small-bowel adult T-cell leukemia/lymphoma with gastric AL amyloidosis

Abstract: An 86-year-old man was admitted because of small-bowel wall thickening and mesenteric lymphadenopathy. Neither peripheral lymphadenopathy nor hepatosplenomegaly was noted. The leukocyte count was 7930/mm 3 , and no abnormal lymphocytes were found. The result of testing for serum antihuman T-lymphotropic virus type 1 (HTLV-1) antibody was positive. A bone marrow biopsy was normal without evidence of lymphoid infiltration. Smallbowel enteroclysis demonstrated a narrowing, edematous lesion with multiple ulceratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Ishibashi et al reported that gastric, small intestinal, and large intestinal ATLL lesions were present in 66%, 18%, and 16% of cases, respectively [ 125 ]. ATLL of primary GI origin without leukemic changes or systemic lymphadenopathy has also been reported [ 126 , 127 , 128 , 129 , 130 ].…”
Section: Differential Diagnoses and Diagnostic Pitfallsmentioning
confidence: 99%
“…Ishibashi et al reported that gastric, small intestinal, and large intestinal ATLL lesions were present in 66%, 18%, and 16% of cases, respectively [ 125 ]. ATLL of primary GI origin without leukemic changes or systemic lymphadenopathy has also been reported [ 126 , 127 , 128 , 129 , 130 ].…”
Section: Differential Diagnoses and Diagnostic Pitfallsmentioning
confidence: 99%